2011
DOI: 10.1002/eet.566
|View full text |Cite
|
Sign up to set email alerts
|

Community Forestry and Forest Conservation: Friends or Strangers?

Abstract: This paper is a meta-study of local forest management experiences in developing countries drawn from a review of 56 case-studies presented in 52 papers. Many case-studies report positive links between community forestry and forest conservation. In international organizations and NGOs there is a generally accepted agreement that collective management (community forestry) will yield success in forest conservation. However, the claim is seldom rigorously examined. We suggest to have a review of the literature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Bowler et al (2010) provided another meta-analysis of 42 peerreviewed articles that came to a similar conclusion, finding that community-based management was associated with greater tree density and basal area but not with other indicators of global environmental benefits (e.g., biodiversity). Casse and Milhøj (2011) is yet another meta-study of local forest management experiences in developing countries drawn from 56 case studies presented in 52 papers. They began with a few astute observations: (1) many case studies report positive links between community forestry and forest conservation; and (2) international organizations and NGOs generally agree that community forestry will yield success in forest conservation; but (3) the claim is seldom rigorously examined.…”
Section: Meta Analyses Of Case Studiesmentioning
confidence: 99%
“…Bowler et al (2010) provided another meta-analysis of 42 peerreviewed articles that came to a similar conclusion, finding that community-based management was associated with greater tree density and basal area but not with other indicators of global environmental benefits (e.g., biodiversity). Casse and Milhøj (2011) is yet another meta-study of local forest management experiences in developing countries drawn from 56 case studies presented in 52 papers. They began with a few astute observations: (1) many case studies report positive links between community forestry and forest conservation; and (2) international organizations and NGOs generally agree that community forestry will yield success in forest conservation; but (3) the claim is seldom rigorously examined.…”
Section: Meta Analyses Of Case Studiesmentioning
confidence: 99%
“…Community forestry is an increasingly important form of forest management (FAO, 2010) and has developed in response to concerns that centralised forest ownership in developing countries has failed to promote sustainable management (Schusser, 2013;Maryudi et al, 2012;Casse and Milhøj, 2011;Sunderlin, 2006). As a broad approach to combating forest degradation, shifting forest ownership from governments to local communities has become a global trend (White and Martin, 2002;Bixler, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…A disadvantage of these studies has been their narrow focus (e.g. forest conservation, Casse and Milhøj, 2011;participation, Chhetri et al, 2013; elite benefit capture, Persha and Andersson, 2014) or discovery of a large number of independent variables (e.g. 43 independent variables, Padgee et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Relying on perceptions is not uncommon. In a meta-study of 52 articles comparing community forestry and forest conservation, Casse and Milhøj [46] found that 21 depended on perception based assessments of forest changes. When comparing forest conservation outcomes reported in the studies (positive, ambiguous, negative, none), they find no significant difference between inventory, remotely sensed, and perception based data.…”
Section: Enforcementmentioning
confidence: 99%